The gist and the content of the informatization of the State Aviation Service of Ukraine - Горбатюк, Яна Вадимівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article analyzes the legal definition and scientific approaches to the understanding of the informatization, the gist and the content of the informatization of the State Aviation Service of Ukraine. The purpose of this article is to find out the gist and content of informatization of the State Aviation Service of Ukraine as a separate activity of state bodies. The Ukrainian science does not have the works, that would be dedicated to solving complex problems of the informatization of the central authorities, including the State Aviation Service of Ukraine. The proper use of the term «informatization» as one of the key elements of the information society need the sufficient scientific justification and the legislative strengthening.